2008
DOI: 10.1016/j.hrthm.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells in the heart: What's the buzz all about?—Part 1: Preclinical considerations

Abstract: New approaches for cardiac repair have been enabled by the discovery that the heart contains its own reservoir of stem cells. These cells are positive for various stem/progenitor cell markers, are selfrenewing, and exhibit multilineage differentiation potential. Recently we developed a method for ex vivo expansion of cardiac-derived stem cells from human myocardial biopsies with a view to subsequent autologous transplantation for myocardial regeneration. Here we review the state of the cardiac stem cell field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 39 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…Knowledge on timing stem cell therapy could therefore have vast consequences for further stem cell research and clinical applications when the time it takes to prepare the treatment exceeds the window of opportunity. Harvesting, culturing, and transplanting autologous cardiac stem cells takes at least 3 weeks [1] and, although these techniques show progress, this might be longer than wished for. Similarly, creating induced pluripotent stem cells through the reprogramming of somatic cells takes approximately 3–4 weeks [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge on timing stem cell therapy could therefore have vast consequences for further stem cell research and clinical applications when the time it takes to prepare the treatment exceeds the window of opportunity. Harvesting, culturing, and transplanting autologous cardiac stem cells takes at least 3 weeks [1] and, although these techniques show progress, this might be longer than wished for. Similarly, creating induced pluripotent stem cells through the reprogramming of somatic cells takes approximately 3–4 weeks [60].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies investigating different kinds of stem and progenitor cells in animal models of MI have shown promising results obtained with cardiac stem cells [1], embryonic stem cells [2,3], skeletal myoblasts [4], and bone-marrow-derived stem cells (BMSCs) [5,6,7], although skeletal myoblasts have later been shown to be arrythmogenic [8] and when further investigating this cell line extreme caution should be in place. While much of the research is still in the preclinical phase, BMSC therapy after MI was shown to be successful in a recent systematic review of clinical trials [9].…”
Section: Introductionmentioning
confidence: 99%
“…All CSCs populations contain most properties of stem cells: self-renewal, multi-lineage differentiation, and clonogenic potentials. CSCs can improve heart function after transplantation [9].…”
mentioning
confidence: 99%
“…Among these, cells expressing stem cell factor receptor c-Kit (CD117) [Beltrami et al, 2003], stem cell antigen-1 (Sca1) [Oh et al, 2003], and homeodomain transcription factor islet-1 (Isl1) [Laugwitz et al, 2005], SP cells [Pfister et al, 2005], and cells able to grow in cardiospheres [Messina et al, 2004] have been suggested to be capable of differentiation into cardiomyocytes, either in vivo or in vitro. Several studies are ongoing, but a clinically feasible method for isolating and expanding human CSC for application during an injury event is still lacking [Smith et al, 2008].…”
mentioning
confidence: 99%